Constitutive and Nitrogen Catabolite Repression-sensitive Production of Gat1 Isoforms - Rai, Rajendra (American Society for Biochemistry and Molecular Biology, 2014)
Nitrogen catabolite repression (NCR)-sensitive transcription is activated by Gln3 and Gat1. In nitrogen excess, Gln3 and Gat1 are cytoplasmic, and transcription is minimal. In poor nitrogen, Gln3 and Gat1 become nuclear and activate transcription. A long standing paradox has surrounded Gat1 production. Gat1 was first reported as an NCR-regulated activity mediating NCR-sensitive transcription in gln3 deletion strains. Upon cloning, GAT1 transcription was, as predicted, NCR-sensitive and Gln3- and Gat1-activated. In contrast, Western blots of Gat1-Myc(13) exhibited two constitutively produced species. Investigating this paradox, we demonstrate that wild type Gat1 isoforms (IsoA and IsoB) are initiated at Gat1 methionines 40, 95, and/or 102, but not at methionine 1. Their low level production is the same in rich and poor nitrogen conditions. When the Myc(13) tag is placed after Gat1 Ser-233, four N-terminal Gat1 isoforms (IsoC–F) are also initiated at methionines 40, 95, and/or 102. However, their production is highly NCR-sensitive, being greater in proline than glutamine medium. Surprisingly, all Gat1 isoforms produced in sufficient quantities to be confidently analyzed (IsoA, IsoC, and IsoD) require Gln3 and UAS(GATA) promoter elements, both requirements typical of NCR-sensitive transcription. These data demonstrate that regulated Gat1 production is more complex than previously recognized, with wild type versus truncated Gat1 proteins failing to be regulated in parallel. This is the first reported instance of Gln3 UAS(GATA)-dependent protein production failing to derepress in nitrogen poor conditions. A Gat1-lacZ ORF swap experiment indicated sequence(s) responsible for the nonparallel production are downstream of Gat1 leucine 61.